CARBIMAZOLE-INDUCED AGRANULOCYTOSIS WITH CONCURRENT SCRUB TYPHUS - Oon, Jen Hoong; Kamarudin, Afifah; Ahmad, Nurul Thohirah; Yong, Lit Sin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION While carbimazole is an effective treatment for hyperthyroidism, it carries a risk of agranulocytosis. Concurrently, rickettsial infections like scrub typhus can worsen neutropenia. We reviewed case notes, investigation results, imaging studies and treatment options based on a literature review. CASE A 55-year-old male farmer with hyperthyroidism on highdose carbimazole treatment sustained a machete injury to his left middle finger. Upon presentation, he had fever, normal thyroid function, stable hemodynamics, severe neutropenia (total white count 0.4 × 109 /L, absolute neutrophil count 0.02 × 103/µL) and typhus eschars. He was treated with doxycycline, piperacillin-tazobactam and subcutaneous granulocyte-colony stimulating factor (G-CSF). Abnormal thyroid function (FT4 46 pmol/L and TSH <0.01 m IU/L) and elevated C-reactive protein (234 mg/L) were also observed. Carbimazole was discontinued and replaced with oral cholestyramine and lithium. Positive serologic findings confirmed scrub typhus. With targeted treatment and G-CSF support, the patient's condition improved, as evidenced by normalized blood counts. Radioactive iodine therapy was contemplated once thyroid function was controlled. CONCLUSION Carbimazole carries the risk of severe adverse effects, including agranulocytosis. This risk may be compounded with a concurrent rickettsial infection, which can also cause neutropenia. Diagnosis relies on clinical suspicion and profound neutropenia, requiring thorough evaluation including serological tests and PCR to differentiate between agranulocytosis-related and rickettsial infections. Immediate discontinuation of carbimazole and replacement with alternative antithyroid drugs is necessary, often supplemented with broad-spectrum antibiotics and G-CSF to prevent overwhelming infection risks. Tailored antibiotic therapy should also be administered for the rickettsial infection. Prompt recognition and intervention are crucial, particularly in endemic areas. Early diagnosis and aggressive management can help mitigate morbidity and mortality. Educating patients on symptom recognition remains the most effective preventive measure.